Transfers, behavior change communication, and intimate partner violence: Post-program evidence from rural Bangladesh - Roy, Shalini; Hidrobo, Melissa; Hoddinott, John F.; Ahmed, Akhter (University Press Limited, 2021)
Intimate partner violence (IPV) is a major global public health problem with economic costs ranging from 1-4 percent of GDP (García-Moreno et al. 2015; Ribero and Sánchez 2005). IPV has multiple malign consequences for women’s physical and mental health (Ellsberg et al. 2008; Kapiga et al. 2017) and is the leading cause of women’s death by homicide (Devries et al. 2013). Adverse effects are transmitted inter-generationally, with IPV linked to poorer child development, nutrition, and health outcomes, as well as a greater likelihood of children also entering into abusive relationships (Aizer 2010; Fulu et al. 2017; Hasselmann and Reichenheim 2006; Karamagi et al. 2007; Koenen et al. 2003; Pollak 2004; Yount et al. 2011). Using data from 141 studies from 81 countries, Devries et al. (2013) estimate that 30 percent of all adult women have experienced physical or sexual IPV. There is considerable regional variation in this prevalence, with South Asia (41 percent)—the region of our study—among the highest in the world.